Will wealth become more concentrated in Europe? Evidence from a calibrated neo-Kaleckian model - Stefan Ederer; Miriam Rehm (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2017)
We develop and calibrate an analytical growth model in the neo-Kaleckian tradition with an endogenous wealth distribution and differential returns to wealth between workers and capitalists. We show that a long-run equilibrium allows for non-zero wealth owned by workers, even as the model contains the ?triumph of the rentier? predicted by Piketty's r > g as a special case. The model's calibration to ten European countries shows that the distribution of wealth is likely to become more unequal in all cases, barring political countermeasures.
Keywords: 330